COVID-19: Effects of lockdown on adenotonsillar hypertrophy and related diseases in children. (November 2020) - Gelardi, M.; Giancaspro, R.; Fiore, V.; Fortunato, F.; Cassano, M.
Abstract: Background: In response to the coronavirus pandemic 2019 (COVID-19), Italy established the national school closings from March 5, 2020. It has been shown that during school closures, there are significant decreases in the diagnoses of the respiratory infections. This has brought as well to a reduction in all those symptoms related to adenotonsillar hypertrophy. Methods: The study included 162 children, aged between 3 and 13 years, waiting for adenoidectomy and/or tonsillectomy, eventually combined with tympanocentesis or tube insertion. Parents have been called to answer a telephone interview aimed at detecting how the symptoms related to adenotonsillar hypertrophy were changing during lockdown. Results: There was an improvement in the overall symptomatology of children during the lockdown period. The value attributed by parents to the children's general assessment during the lockdown period decreased significatively during the quarantine (p = 0, 0000). Conclusions: The present study demonstrates that lockdown can have a positive impact on those specific diseases derived from precocious socialization and that it results to be particularly effective for the most vulnerable children. Indeed, lockdown has resulted to be so efficient that it has caused a modification in a medical and surgical therapeutic indication.